(untitled) (CIPEEX, 2025)
The objective of this summary was to present the main differences between innate and acquired immune responses. Understanding the immune response is extremely important for developing immune therapies and evaluating the body’s protective mechanisms against infections. The innate immune response is immediate and non-specific, mediated by cells like macrophages and neutrophils that act rapidly after detecting pathogens via pattern recognition receptors and cytokines. Acquired immunity, on the other hand, is highly specific, involving B and T lymphocytes, and is characterized by immunological memory, enabling more efficient responses in subsequent exposures. Innate immunity acts quickly to infections using physical (skin, cilia), chemical (cathelicidins, defensins), and cellular barriers (macrophages, neutrophils, NK cells). This immunity does not require prior exposure and lacks memory. In contrast, acquired immunity develops after exposure to a pathogen, progresses slowly, and involves humoral and cellular responses through antibodies and cytotoxic T-helper cells, respectively. The innate immune system activates and modulates the acquired immune response, which eliminates the pathogen and creates memory for future exposures. Imbalances in these systems can cause autoimmune diseases, allergies, and immunodeficiencies. Understanding these interactions is crucial for developing new therapies.